STRUKTUR KOMUNITAS IKAN KARANG DI PERAIRAN SEKUNYIT KECAMATAN KAUR SELATAN KABUPATEN KAUR - ZAMDIAL T (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2013)
The aim of this research is to know the community structure of coral fish in Sekunyit waters South Kaur District, Regency of Kaur. This research was conducted at 3 m depth on the west continental shelf of South Kaur Disrict. Data of coral reef fishes was obtained with Visual Census Method that used Reef Resources Assessment (RRA) Method that was depeloved from Manta Tow Method. This research focused on species abundance, diversity indexs (H), dominance index (C) and uniformity index (E): Abundance of coral reef fishes at Sekunyit Waters is 4.987 fish/ha consists of 79 species arid 17 families. Under the category of mayor fish is obtained as many as 6 families major fish with 39 species, 12_ families target fish with 29 and l families indicator fish with 11 species. The data analysis of coral reef fishes· condition was determined with diversity index (H ')= 3.91, dominance index (C) = 0.03 and uniformity index (E) = 0.85. The value of diversity, dominance and uniformity indexs showed that the communities of coral reef fishes and waters condition at Sekunyit Waters is stable